Penyuluhan Legalitas Produk Pirt dan Keamanan Pangan bagi Kelompok Wanita Tani di Kecamatan Tengaran Kabupaten Semarang: Counseling on The Legality of Pirt Products and Food Safety For Farmer Women's Group in Tengaran Semarang District - Bambang Hermanu; Enny Purwati Nurlaili; Jonathan; Melanita Kristiani; Miranti Mandasari (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
In general, the development of the Integrated Security System (SKPT) in its implementation still experiences synergistic weaknesses between the networks formed, and actually tends to affect the level of effectiveness. This has resulted in many processed food products, especially PIRT that do not have distribution permits, due to various factors and constraints that occur in the field, in addition to law enforcement that is still not optimal, especially those related to the implementation of distribution permit provisions that have not been able to reach all producer communities. PIRT. With the socialization of the PIRT distribution permit, it is hoped that it can further increase the effectiveness of the implementation of the food safety system, which at the same time seeks efforts to improve the SKPT as an ideal and effective policy format, and qualitatively can also further enhance efforts to protect food consumers.